Multimedia networking technologies, protocols, and architectures - Vidal, Ivan (Artech House, 2019)
Providing a survey on the technologies, protocols, and architectures that are widely used in practice to implement networked multimedia services, this book contains questions and exercises to provide the reader with insight on the practical application of the explained concepts. -- Edited summary from book.
Keywords: Multimedia systems.; Computer networks.; elektronické knihy; electronic books